2008
DOI: 10.1177/1077801208323793
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and Contraceptive Use in a Rural Indian Village

Abstract: This study uses qualitative methods to examine how domestic violence affects the use of contraceptives by women in a rural village in India. The study highlights how multilevel factors are linked to a woman's ability to contracept and make fertility decisions in a context where being a wife implies obedience, limited mobility, sexual availability, and high fertility. The authors find that violence is normalized, or considered acceptable, if women do not adhere to expected gender roles. Although women's ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…These findings are largely consistent with other studies conducted in Pakistan [11,14,15], India [5], and Bangladesh [4,20], although it is difficult to compare the prevalence because of variations in definitions and methodology.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are largely consistent with other studies conducted in Pakistan [11,14,15], India [5], and Bangladesh [4,20], although it is difficult to compare the prevalence because of variations in definitions and methodology.…”
Section: Discussionsupporting
confidence: 93%
“…Arguably, IPV may undermine reproductive health in many ways: it may create a climate of fear that makes it difficult for women to negotiate the use of contraceptives with their husbands [3,5,6] or to get proper prenatal care. The women who are victims of IPV might experience unintended pregnancies [2,6], abortions [3,7], and gynecologic disorders such as irregular vaginal bleeding [1,8], genital injury, dysmenorrhea [8], sexually transmitted infections [1], and sexual dysfunction [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with other studies which found that DV has significant negative implications for women's reproductive health (Campbell 2002;Wilson-Williams et al 2008). It is argued that improved socio-economic status of rural women is a prerequisite to improve their reproductive health status in Pakistan (Fatmi and Avan 2002).…”
Section: Domestic Violence and Women's Healthsupporting
confidence: 92%
“…Specific norms regarding violence are essential to consider, as they are directly related to the exercise of violence against women (Moore, 1999;Koenig et al, 2006;Sarkar, 2008;OECD, 2010;Stephenson et al, 2012) and are more susceptible to "create a climate of fear and intimidation" (Gilfus et al, 2010;Nanda et al, 2013). Intimate-partner violence (IPV) is said to be grounded in patriarchal society that gives primacy and privilege to men (Amoakohene, 2004;Kishor and Subaiya, 2008), and "serves to maintain the unequal balance of power" between men and women (Watts and Zimmerman, 2002;Wilson-Williams et al, 2008). Qualitative research by Hatcher et al (2013) in the province of Nyanza in Kenya has shown that at times violence against women was motivated by what men and the "society" considered as women's challenging of the social norms and of men's authority.…”
Section: Introductionmentioning
confidence: 98%